2005
DOI: 10.1002/micr.20104
|View full text |Cite
|
Sign up to set email alerts
|

Salvage operations of free tissue transfer following internal jugular venous thrombosis: A review of 4 cases

Abstract: The internal jugular vein (IJV) is used as the optimal recipient for free-tissue transfer in reconstruction following modified radical neck dissection. Some reports documented rare cases of flap compromise following IJV thrombosis, but large sample studies are few. We present cases of emergent exploration and an analysis of factors to improve salvage rates of compromise due to IJV thrombosis. From a survey of 756 patients, four developed congestion due to IJV thrombosis and returned to the operating room. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Brown et al 25 and de Bree et al 26 reported up to 24% occult IJV thrombosis after neck dissection. Even if recanalization of the IJV is likely in long-term followup, 27 this complication can lead to flap loss, as described by Miyasaka et al 28 The choice of the recipient site is also challenging in the vessel-depleted neck, after prior neck dissection, or after external radiotherapy. Following multiple neck surgeries, the external jugular vein and IJV can be resected or compromised.…”
Section: Discussionmentioning
confidence: 95%
“…Brown et al 25 and de Bree et al 26 reported up to 24% occult IJV thrombosis after neck dissection. Even if recanalization of the IJV is likely in long-term followup, 27 this complication can lead to flap loss, as described by Miyasaka et al 28 The choice of the recipient site is also challenging in the vessel-depleted neck, after prior neck dissection, or after external radiotherapy. Following multiple neck surgeries, the external jugular vein and IJV can be resected or compromised.…”
Section: Discussionmentioning
confidence: 95%
“…These complications often occur in the first twenty-four hours [1,5,[12][13][14]. This acute period does not allow the creation of a microvascular network, unlike what happens in chronic occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of thrombus should prompt opening the anastomosis and evacuation of the clot with heparinised saline irrigation or a Fogarty catheter prior to careful re anastomosis. (19) Thrombolytic agents, such as streptokinase, urokinase or tissue plasminogen activator, can be used if a thrombus is identified, particularly in the venous system. Their use has been well documented as a means to salvage vascular insufficiency and theoretically prevent irreversible ischemic reperfusion injury or no reflow phenomenon.…”
Section: Discussionmentioning
confidence: 99%